Impact of feed with varying crude protein (CP) levels on growth performance of different fish species cultured under similar regimes - Manzoor, Kashif; Rasool, Fayyaz; Parveen, Shakeela; Hafeez-ur-Rehman, Muhammad; Matiullah; Mahmood, Shahid; Ayub, Amina (International Journal of Applied and Experimental Biology, 2023)
Fish polyculture has resulted in high fish production per unit area, mainly due to the best utilization of all kinds of nutrients. In this nine month’s experimental study, five different fish species were stocked in five earthen ponds designated as control (one pond), treatment-T1 (two ponds) and treatment-T2 (two ponds). Fish stocked in T1 and T2 ponds were fed with a commercial feed containing 20% and 25% crude protein, respectively, whereas fish stocked in the control pond was fed with a conventional mixture of feed ingredients (fish meal, gluten, sunflower, and rice polish) having 20% CP. The fish was fed @ 3% of the fish wet body weight twice a day. The fish was sampled every fortnight. Physicochemical parameters of the ponds were measured daily. The results showed that the maximum weight gain (255 g) was recorded in Pangasius pangasius in treatment T2 and minimum (52.5 g) in Cirrhinus mrigala in the control pond. Overall, maximum fish production was recorded after harvest in treatment T2 followed by that in treatment T1 and control ponds, respectively. Overall, the commercial fish feed enriched with crude protein was very effective in promoting growth and development of pond fish.